Artificial Intelligence in Higher Education: Challenges to the Development of Critical Thinking Among College Students - Al masruroh, Bushtanul Fahmiyah (Maliki Interdisciplinary Journal, 2026)
The integration of artificial intelligence (AI) into higher education is causing profound changes—both as a learning accelerator and as a challenge to students' cognitive development. This study examines the challenges of using AI technology to foster critical thinking in higher education. Through a systematic literature review, the article analyzes how overreliance on AI-based tools—such as large language models (LLMs)—can lead to "cognitive laziness," limit independent problem-solving processes, and impair analytical skills. The findings suggest that while AI offers efficiency in information retrieval and task automation, it also has the potential to generate confirmation bias and diminish the intensity of academic discourse if not properly regulated. Therefore, the study recommends redesigning pedagogy through user-centered blended learning methods, updating assessment tools based on higher-order thinking skills, and strengthening ethical competencies in dealing with AI. In this way, AI can be positioned as a dialogue partner, not a substitute for students' thinking processes.